2019
DOI: 10.1002/brb3.1291
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐9 gene polymorphisms are associated with ischemic stroke severity and early neurologic deterioration in patients with atrial fibrillation

Abstract: Objectives The mechanisms of ischemic stroke severity and early neurologic deterioration (END) are not fully understood. The aim of the present study was to investigate the association of six variants in MMP‐9 gene with ischemic stroke severity and the risk for END in ischemic stroke (IS) patients with atrial fibrillation (AF). Methods This was a multi‐center, prospective, observational study of 615 acute IS patients with AF admitted to six pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Increasing studies demonstrated that polymorphisms of MMP9 were associated with cerebrovascular disease [25, 26]. A lot of studies demonstrated that MMP9 rs3787268 and rs3918242 may increase the risk of IS [27-30]. Simultaneously, Yi et al [31] also found that rs3918242 and rs3787268 were associated with hemorrhagic transformation in acute IS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies demonstrated that polymorphisms of MMP9 were associated with cerebrovascular disease [25, 26]. A lot of studies demonstrated that MMP9 rs3787268 and rs3918242 may increase the risk of IS [27-30]. Simultaneously, Yi et al [31] also found that rs3918242 and rs3787268 were associated with hemorrhagic transformation in acute IS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, 181.7 ng/mL was used as the cutoff value of MMP-9, with a positive predictive value of 48% and a negative predictive value of 96%. Considering MMP-9 activity is controlled by single nucleotide polymorphisms (SNPs) of the MMP-9 gene, Yi et al (2019) pointed out that MMP-9 polymorphisms were independently associated with a higher risk of END in AIS patients with AF. In conclusion, MMP-9 is essential to HT after AIS, and further studies are needed to confirm the diverse mechanisms of MMP-9 in AIS.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset contains the raw data (supplementary Table), frequencies of alleles and genotypes ( Table 1 ) for three SNPs of two MMP genes (rs1799750 MMP1 , rs3918242 and rs17576 MMP9 ) in Russian patients diagnosed with POAG, EH, and PU. These polymorphisms were previously reported for their association with POAG, EH, and PU ( Table 2 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . The studied SNPs manifest the regulatory potential ( Table 3 ), which is evidenced by several eQTLs ( Table 4 ) and splicing QTLs ( Table 5 ).…”
Section: Data Descriptionmentioning
confidence: 89%